A framework for work-based learning: basic pillars and the interactions between them. Issue 1 (8th February 2016) - Ferrández-Berrueco, Reina; Kekale, Tauno; Devins, David
Abstract : Purpose: – European policy is placing an increasing emphasis on involving employers and labour market institutions in the design and delivery of higher education (HE) programmes that match curricula to current and future needs of the economy. The purpose of this paper is to investigate the curriculum development process for work-based learning (WBL) programmes and to connect it to the basic pillars, organizational and pedagogical strategies and key stages that enable higher education institutions (HEIs) to foster students' learning, employability and innovation. Design/methodology/approach: – Case studies of 14 European WBL programmes in HE are reported using interviews and document analysis. These case studies are used to develop a final framework and examples of practice. Findings: – A framework was designed to develop WBL programmes that include three basic pillars and the interactions between them to enhance learning quality (doctrine), provide authentic experiences (authenticity) and respect the ways of developing and delivering WBL (culture). Research limitations/implications: – While selecting the cases on this "best practices" basis, some important pitfalls were not discussed. Thus, rather than offering a definitive theory, the authors provide a framework of issues that should at least be taken into account in the different stages of planning, delivery and reflection. Practical implications: – The framework is simultaneously a kind of "checklist" for WBL curriculum developers. Originality/value: – The research presents 14 case studies from programmes recognized in six European countries and develops an original WBL programme planning, delivery and evaluation framework that can also be used as a checklist for HEIs offering WBL programmes.